Micro Plastic Pollution in South Asia: The Impact of Plastic Pollution over the Unsustainable Development Goals - Tasfiea Rifa; Mohammad Belayet Hossain (Lex Publica, 2022)
One of the most pressing environmental issues facing the world right now is plastic waste. Once in the environment, plastics continuously degrade into microplastics, which are fragments of plastic. There are more national and international promises to reduce microplastic pollution as the world's plastic production rises. National governments are increasingly banning single-use plastic products or imposing taxes on them. Consider the UN Sustainable Development Goals, the UN Environment Assembly Resolutions on Marine Litter and Microplastics, and Addressing Single-Use Plastic Products Pollution as examples of these commitments. In 2015, the UN announced the adoption of 17 Sustainable Development Goals (SDGs). In an effort to increase their sustainability, the SDGs have been extensively adopted by governments and businesses. There are 17 SDGs, comprising 169 targets, which are measurable against 247 unique indicators but there is only one indicator under Goal 14, specifically related to reducing impacts from microplastics. There are various international and regional legal policies which have provisions that indicate plastic pollution but none of them have mentioned microplastic pollution. There are some recent national legislations regarding microplastic pollution. This paper briefly discusses the concept of microplastics and the situation of microplastics pollution in selected South Asian countries including India, Bangladesh, Maldives, Sri Lanka and Pakistan. There is a brief overview of international and regional legal policies along with litigations are cultivated in this paper. The paper also analyzes the impact of plastic pollution over The Un Sustainable Development Goals.   Abstrak. Salah satu masalah lingkungan paling mendesak yang dihadapi dunia saat ini adalah sampah plastik. Begitu berada di lingkungan, plastik terus terdegradasi menjadi mikroplastik, yang merupakan pecahan plastik. Ada lebih banyak janji nasional dan internasional untuk mengurangi polusi mikroplastik saat produksi plastik dunia meningkat. Pemerintah nasional semakin melarang produk plastik sekali pakai atau mengenakan pajak pada mereka. Pertimbangkan Tujuan Pembangunan Berkelanjutan PBB, Resolusi Majelis Lingkungan PBB tentang Sampah Laut dan Mikroplastik, dan Mengatasi Polusi Produk Plastik Sekali Pakai sebagai contoh dari komitmen ini. Pada 2015, PBB mengumumkan adopsi 17 Tujuan Pembangunan Berkelanjutan (SDGs). Dalam upaya meningkatkan keberlanjutannya, SDGs telah diadopsi secara luas oleh pemerintah dan bisnis. Ada 17 SDGs, yang terdiri dari 169 target, yang dapat diukur dengan 247 indikator unik, tetapi hanya ada satu indikator di bawah Tujuan 14, khususnya terkait pengurangan dampak mikroplastik. Terdapat berbagai kebijakan hukum internasional dan regional yang memiliki ketentuan yang mengindikasikan pencemaran plastik namun belum ada satupun yang menyebutkan pencemaran mikroplastik. Ada beberapa undang-undang nasional baru-baru ini  mengenai polusi mikroplastik. Makalah ini membahas secara singkat konsep mikroplastik dan situasi polusi mikroplastik di negara-negara Asia Selatan tertentu termasuk India, Bangladesh, Maladewa, Sri Lanka, dan Pakistan. Ada gambaran singkat tentang kebijakan hukum internasional dan regional beserta litigasi yang digarap dalam tulisan ini. Makalah ini juga menganalisis dampak polusi plastik terhadap Tujuan Pembangunan Berkelanjutan PBB.   Kata kunci: Mikroplastik, polusi, sampah plastik, tujuan pembangunan berkelanjutan.